Respuesta :

X= -1/6, 2
Hope that helps

Answer:

Step-by-step explanation:

Please be specific:  "How do you solve 6x^2 - 2 = 11x?"

Rewrite this in terms of descending powers of x:  6x^2 - 11x - 1 = 0.

Use the quadratic formula to find the roots.  Here the coefficients are a = 6, b = -11 and c = -1.  Then the discriminant b^2 - 4ac becomes 121 - 4(6)(-1) = 121 + 24 = 145, and so the roots are:

       -(-11) ± √145          11 ± √145

x = ---------------------- = ------------------

             2(6)                       12